Algebra 2

posted by .

Condense the expressions

1) 10 log x + 2 log 10
2) 1og base 5 of 8 - log base 5 of 12

Can you please explain to me how do you condense these expressions? Thanks in advanced!

  • Algebra 2 -

    10logx = log(x^10)
    2log10 = log 10^2

    10logx + 2log10 = log 100x^10

    log8 - log 12 = log (8/12) = log(2/3)

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. math

    write as a single logarithm: -2logbase3(1/x)+(1/3)logbase3(square root of x) please show the steps to solving this. thanx. remember that 1 log (AxB) = log A + Log B (same base) 2 log (A/B) = log A - log B 3 log A^n = n log A use these …
  2. Logarithms

    CONDENSE INTO THE LOG OF A SINGLE QUANTITY: (1) Base 7 2/3 log( z - 2 ) (2) 2 ln8 + 5 ln( z - 4 ) (3) Base 4 1/2 [ log( x + 1 ) + 2 log( x - 1 ) ] + 6 logx
  3. Math Help Please

    Which of the following expressions is equal to log (x sqrt-y)/z^5 A. log x + log (1/2) + log y– log 5 – log z B. log [x + (1/2)y – 5z] C. log x + (1/2)log y – 5 log z d. [(1/2) log x log y]/(5 log z)
  4. math

    Logarithm!!! Select all of the following that are true statements: (a) log(2x) = log(2) + log(x) (b) log(3x) = 3 log(x) (c) log(12y) = 2 log(2) + log(3y) (d) log(5y) = log(20y) – log(4) (e) log(x) = log(5x) – log(5) (f) ln(25) …
  5. Algebra 2

    Can you please explain step by step on how to do this problem?
  6. Algebra 2

    Can you please explain step by step on how to do this problem?
  7. Algebra 2

    Use the laws of logarithms to condense the following expressions. log base 5 of 6 - log base 5 of x
  8. Algebra 2

    Use the laws of logarithms to condense the following expressions. log base 3 of 2 + 2 log base 3 of x
  9. Algebra 2

    -Explain the difference between log base b (mn) and ( log base b of m)(log base b of n). Are they equivalent?
  10. Advanced Functions/ Precalculus Log

    1. Evaluate 4^(log base4 64) + 10^(log100) 2. Write 1+log(base2)x^3 as a single logarithm 3. Write log(base b)√(x^3 y z^6) 4. Solve log(base 2)x-log(base 2)6=log(base 2)5+2log(base 2)3 5. Solve 3^(2x) = 9(81^x) 6. Solve 3^(2x)=7^(3x-1). …

More Similar Questions